2022
DOI: 10.3390/su15010234
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy for Balancing Carbon Emissions and Reducing Carbon Transfer under Global Value Chains: A Way Forward

Abstract: Research on the relationship between a country’s renewable energy consumption and carbon emissions is of great significance for reducing carbon emissions embodied in international trade. There always exists a gap between production-based and consumption-based carbon emissions. Accordingly, this paper investigates the influence of renewable energy consumption on carbon emission balance, the ratio of production-based emissions to consumption-based emissions, in various countries using the ordinary least square (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The obtained results for the EU-27 are in line with other empirical papers. Thus, Guo et al (2022) [55] found that a 1% increase in renewable energy consumption led to a decrease in carbon emission balance of 5.8%. For G7 countries, it was proven that hydroelectric and renewable energy production was able to reduce CO 2 emissions in all regression models [56].…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results for the EU-27 are in line with other empirical papers. Thus, Guo et al (2022) [55] found that a 1% increase in renewable energy consumption led to a decrease in carbon emission balance of 5.8%. For G7 countries, it was proven that hydroelectric and renewable energy production was able to reduce CO 2 emissions in all regression models [56].…”
Section: Resultsmentioning
confidence: 99%
“…Carbon footprint has not yet reached a consensus definition [14], [15], [16] but it is usually recognized as the total amount of carbon dioxide emissions that are directly and indirectly associated with an entire product cycle.…”
Section: Carbon Footprint Classification and Assessment Methodsmentioning
confidence: 99%
“…The ratio of the actual auto to analytical hard bleed-off size can be expressed as a percentage: W% ActualBleedoffCoC19 = W ActualAutoBleedoffCoC19 W AnalysedHardBleedoffCoC19 × 100% = 1. 14 5.616 ×100% =20%…”
Section: Daymentioning
confidence: 99%
“…The MRIO model, which elucidates the mutual interrelation among sectors or regions from the perspective of supply chain, is a prevalent approach for investigating energy [35,36], water [37,38], CO2 emissions [39,40], and other pollutant emissions [41][42][43] embedded within interregional trade. Consistent with Qian et al [16], this study first esti- The MRIO model, which elucidates the mutual interrelation among sectors or regions from the perspective of supply chain, is a prevalent approach for investigating energy [35,36], water [37,38], CO 2 emissions [39,40], and other pollutant emissions [41][42][43] embedded within interregional trade. Consistent with Qian et al [16], this study first estimated the SO 2 emissions attributable to production, consumption, and income using the MRIO model.…”
Section: Multi-regional Input-output (Mrio) Analysismentioning
confidence: 99%